Dry leaf or twig mantis? A new genus and species of Acanthopidae with sexually dimorphic cryptic strategies (Insecta: Mantodea) - Agudelo R., Antonio A.; Maldaner, Caroline; Rafael, José A. (Zootaxa, 2019)
Praying mantises (Mantodea) are distinct for their rich diversity of cryptic adaptations. Among the many strategies, dry-leaf mimicry have evolved multiple times in unrelated lineages from different zoogeographic regions, among them the Neotropical Acanthopidae. Here we describe Metacanthops fuscum n. gen. et n. sp. based on male and female specimens from the Brazilian Amazon. The recognition of this new acanthopid lineage revealed that Acanthops amazonica Beier, 1930 (currently assigned to Metilia Stål) is a member of Metacanthops and thus we transfer this species, now referable to as Metacanthops amazonica (Beier, 1930) n. comb., redescribe the holotype, and provide new data on its distribution in Brazil and French Guiana. Metacanthops is closely related to Metilia, from which its number of forefemoral posteroventral spines, head and compound eye shape, pronotal configuration, wings features, and the entirely brown habitus of males, can distinguish it. We highlight some aspects of sexual dimorphism in Metacanthops fuscum in relation to their dimorphic cryptic strategies, where males resemble a dry leaf and females a lichenous twig. We additionally establish five recently published names under genus Metilia as nomina nuda.